Nanoscale evidence of contrasted processes for root-derived organic matter stabilization by mineral interactions depending on soil depth. (June 2015) - Rumpel, Cornelia; Baumann, Karen; Remusat, Laurent; Dignac, Marie-France; Barré, Pierre; Deldicque, Damien; Glasser, Gunnar; Lieberwirth, Ingo; Chabbi, Abad
Abstract: Up to now stabilization of organic matter (OM) in soils due to mineral interactions has been assessed mainly by correlations between carbon and iron and/or aluminum oxides evidencing that metal oxides may be principal stabilization agents. The nature and morphology of stabilized OM are poorly known. Taking advantage of a field experiment, the aim of our study was to analyze the fate of 13 C and 15 N labeled root material at 30 and 90 cm depths after three years of incubation and to characterize the nature of OM stabilized by interactions with metal oxides. Our methodological approach included isolation of metal oxides by physical fractionation and visualization of their interaction with OM using NanoSIMS. We concentrated metal oxides in a fraction corresponding to our objectives: the heavy fraction (>3 g cm −3 ) of fine silt. NanoSIMS analyses of this fraction allowed us to locate unlabeled OM and OM either double labeled or carrying one single label in association with metal oxides. Our results suggest that decoupling of C and N may have happened during OM stabilization within the timeframe of the 3 year field experiment. Scanning electron microscopy (SEM) after NanoSIMS analyzes, indicated that 15 N labeled OM at 90 cm were well-defined ovoid OM particles resembling to microbial cells in interaction with Fe, Al and Ti oxides. At 30 cm depth, OM associated with metal oxides was 13 C and 15 N labeled unstructured material, possibly derived from plant debris. We suggest that at the two soil depths under investigation different processes might be at work, leading to association of OM with mineral compounds of the isolated fraction: in upper soil layers, decomposed plant material may directly interact with metal oxides, whereas in deep mineral soil, OM could mainly interact with metal oxides after microbial turnover. Both types of interactions may be fairly stable as they persisted after ultrasonication and salt extraction. Graphical abstract: Highlights: Visual demonstration of organic material in interaction with metal oxides rather than demonstration by correlation. Stabilization of root material by interaction with metal oxides occurs in different soil depths within a time frame of years. Decoupling of C and N stabilized by minerals may occur at longer timescales.